Inulin increases the beneficial effects of rhubarb supplementation on high-fat high-sugar diet-induced metabolic disorders in mice: impact on energy expenditure, brown adipose tissue activity, and microbiota. (31st December 2023) - Régnier, Marion; Van Hul, Matthias; Roumain, Martin; Paquot, Adrien; de Wouters d'Oplinter, Alice; Suriano, Francesco; Everard, Amandine; Delzenne, Nathalie M.; Muccioli, Giulio G.; Cani, Patrice D.
ABSTRACT: Consumption of prebiotics and plant-based compounds have many beneficial health effects through modulation of gut microbiota composition and are considered as promising nutritional strategy for the treatment of metabolic diseases. In the present study, we assessed the separated and combined effects of inulin and rhubarb on diet-induced metabolic disease in mice. We showed that supplementation with both inulin and rhubarb abolished the total body and fat mass gain upon high-fat and high-sucrose diet (HFHS) as well as several obesity-associated metabolic disorders. These effects were associated with increased energy expenditure, lower whitening of the brown adipose tissue, higher mitochondria activity and increased expression of lipolytic markers in white adipose tissue. Despite modifications of intestinal gut microbiota and bile acid compositions by inulin or rhubarb alone, combination of both inulin and rhubarb had minor additional impact on these parameters. However, the combination of inulin and rhubarb increased the expression of several antimicrobial peptides and higher goblet cell numbers, thereby suggesting a reinforcement of the gut barrier. Together, these results suggest that the combination of inulin and rhubarb in mice potentiates beneficial effects of separated rhubarb and inulin on HFHS-related metabolic disease and could be considered as nutritional strategy for the prevention and treatment of obesity and related pathologies.